2011
DOI: 10.1590/s1413-70542011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of water deficit on rapeseed (Brassica napus L.) crop

Abstract: Effects of different levels of water deficit applied during rapeseed crop development were assessed in a trial with metallic pots in greenhouse at the Department of Agricultural Engineering of Kassel University, Witzenhausen, Germany. A randomized block design was used with one cultivar (Ability Summer Rape) and three levels of water deficit (0, 30, and 60% of evapotranspiration) in three treatments and 20 replicates. Irrigation management was carried out through daily water balance, where ET = I - D; ET: evap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
5
11
0
6
Order By: Relevance
“…It is the practice of deliberately under-irrigating crops to reduce water consumption while minimizing adverse effects of extreme water stress on yield (Ayana, 2011). Deficit irrigation does not always decrease yield, as deficits properly applied in some development stages may even increase crop yield (Bilibio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is the practice of deliberately under-irrigating crops to reduce water consumption while minimizing adverse effects of extreme water stress on yield (Ayana, 2011). Deficit irrigation does not always decrease yield, as deficits properly applied in some development stages may even increase crop yield (Bilibio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bilibio et al (2011), Dogan et al (2011, Kamkar et al (2011) and Sharghi et al (2011) studied the effects of different levels of water stress (0, 30 and 60% of canola crop evapotranspiration) and found that number of branches, number of pods, dry weight, yield and oil content were significantly affected. Istanbulluoglu et al (2010) evaluated the effect of supplemental irrigation applied at different stages of canola development and found Regarding different levels of nitrogen, we found significant differences in dry weight, thousand grain weight and oil content in 2012 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Valores de tensão de água no solo para a cultura da canola com e sem irrigação ;(R 0,99 e P 0,01) 1 (0,5485 ) Na terceira e última coleta (Tabela 6) os resultados de AP são condizentes, pois, foram encontrados resultados significativos com irrigação superior a 1,2 m (Kirkegaard et al, 2012;EL-Howeity & Asfour, 2012;Dogan et al, 2011) e o NSP é reafirmado por Bilibio et al (2011).…”
Section: Resultsunclassified